2022
DOI: 10.3390/life12101630
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry (Morus alba L.) Leaf Extract and 1-Deoxynojirimycin Improve Skeletal Muscle Insulin Resistance via the Activation of IRS-1/PI3K/Akt Pathway in db/db Mice

Abstract: Mulberry (Morus alba L.) leaves have been used to lower blood glucose in patients with diabetes. We evaluated the effects of mulberry leaves extract (MLE) and 1-deoxynojirimycin (1-DNJ) in improving insulin resistance through the activation of the IRS-1/PI3K/Akt pathway in the skeletal muscle of db/db mice. Histological analysis revealed an amelioration of muscle deformation and increased muscle fiber size. MLE and 1-DNJ positively raised the protein expression of related glucose uptake and increased the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Although insulin is produced in vivo, the cells use insulin inefficiently, leading to hyperglycemia. 16,17 Hyperglycemia can induce oxidative stress and aggravate IR in surrounding tissues, leading to metabolic syndrome. This can result in retinopathy, nephropathy, and neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Although insulin is produced in vivo, the cells use insulin inefficiently, leading to hyperglycemia. 16,17 Hyperglycemia can induce oxidative stress and aggravate IR in surrounding tissues, leading to metabolic syndrome. This can result in retinopathy, nephropathy, and neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that dexamethasone induces thinning of muscle fibers through decreased muscle protein synthesis and increased degradation, resulting in decreased muscle strength due to a decrease in muscle mass [ 41 - 43 ]. MA attenuates insulin resistance in skeletal muscle by activating the insulin receptor substrate-1/PI3K/Akt signaling pathway [ 44 ], and flavonoids derived from MA have been associated with improvements in type 2 diabetes through enhanced mitochondrial function in the muscle [ 45 ]. According to previous studies, AK and compounds from AK inhibit muscle wasting by promoting myogenesis [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main ingredients of the formulated treatment feed were Morus alba leaves along with hydrolyzed chicken, oats, hydrolyzed dried chicken, chicken fat, powdered cellulose, oats, bit pulp, inulin, omega 3, vitamins C and E, and a mineral premix (calcium, potassium, magnesium, carbohydrate, and salt). As shown in previous mouse experiments, the amount Morus alba leaves used in this study was determined based on the amount of 1-deoxynojirimycin [ 60 ]. Unlike previous mouse experiments, this pet food used hydrolyzed Morus alba leaf powder.…”
Section: Methodsmentioning
confidence: 99%